Cover Feature: Isomerization of Allylic Alcohols to Ketones Catalyzed by Well‐Defined Iron PNP Pincer Catalysts (Chem. Eur. J. 16/2018). Issue 16 (29th January 2018) - Xia, Tian; Wei, Zhihong; Spiegelberg, Brian; Jiao, Haijun; Hinze, Sandra; de Vries, Johannes G.
Abstract : A well‐defined iron pincer complex has been successfully applied for the isomerization of allylic and homo‐allylic alcohols to the corresponding ketones. A range of differently substituted aromatic as well as aliphatic allylic alcohols are suitable candidates. The addition of KO t Bu leads to the formation of the active catalyst, which performs the isomerization by a two‐step self‐hydrogen‐borrowing process. The mechanism was verified using DFT calculations. More information can be found in the Full Paper by J. G. de Vries, et al. onpage 4043 .